Household leveraging and deleveraging - Alejandro Justiniano; Giorgio E. Primiceri; Andrea Tambalotti (Federal Reserve Bank of New York, 2013)
U.S. households' debt skyrocketed between 2000 and 2007, but has since been falling. This leveraging and deleveraging cycle cannot be accounted for by the liberalization and subsequent tightening of mortgage credit standards that occurred during the period. We base this conclusion on a quantitative dynamic general equilibrium model calibrated using macroeconomic aggregates and microeconomic data from the Survey of Consumer Finances. From the perspective of the model, the credit cycle is more likely due to factors that impacted house prices more directly, thus affecting the availability of credit through a collateral channel. In either case, the macroeconomic consequences of leveraging and deleveraging are relatively minor because the responses of borrowers and lenders roughly wash out in the aggregate.
Keywords: E21; E32; 330; household debt; house prices; mortgages; Private Verschuldung; Hypothek; Konjunktur; Allgemeines Gleichgewicht; Theorie; USA